Reflex Decay Test Can Reveal Ear Involvement in Fabry Disease. Issue 5 (September 2021) - Kiykim, Ertugrul; Kaya, Melda; Dincer, Mevlut Tamer; Bakir, Alev; Alagoz, Selma; Aktuglu Zeybek, Ayse; Gulcicek, Sibel; Seyahi, Nurhan; Trabulus, Sinan; Atas, Ahmet
Abstract : Objectives: Fabry disease (FD) is an X-linked lysosomal storage disorder that causes multisystem involvement, including ear disease. In this study, we aimed to investigate the nature of auditory issues in FD using a wide spectrum of audiological tests. Design: This cross-sectional study was conducted between June 2017 and December 2018. We collected the clinical and laboratory data of 40 eligible FD patients, 45 healthy subjects, and 26 diabetic controls. All patients and controls completed audiologic evaluations that included tympanometry, acoustic reflex threshold test, reflex decay test, pure-tone audiometry, speech audiometry, transient otoacoustic emissions (TEOAEs), high-frequency audiometry, and distortion product otoacoustic emission (DPOAE). Results: In our study population, hearing was reduced at higher frequencies starting at 4 kHz in both the FD and diabetic groups. Regarding the acoustic reflex threshold test, FD and diabetic patients had similar results. In all frequencies, positive decay was significantly more frequent in FD patients when compared with the diabetic patients and healthy controls ( p < 0.001 for each ear). The FD patients and healthy controls had similar results for DPOAE testing. Conclusions: We showed that FD patients had a higher rate of reflex decay, indicating retrocochlear involvement. Thus, further investigation of factors associated with retrocochlear involvement could be investigated, such as ABR and speech in noise tests. Abstract : Supplemental Digital Content is available in the text.